The Evolution of Electrical Engineering: A Review of Breakthroughs in Power Systems, Automation, and Renewable Energy Integration - Sinha, Muskan (Journal of Advanced Research in Electrical Engineering and Technology, 2025)
Electrical engineering has undergone transformative advancements over the past century, significantly reshaping industries and enabling sustainable development on a global scale. From the electrification of rural areas to the integration of intelligent automation systems, the field has consistently pushed technological boundaries to address society's evolving needs. This review explores key breakthroughs in three critical areas: power systems, automation, and renewable energy integration. In the realm of power systems, advancements such as smart grids, high-voltage direct current (HVDC) transmission, and innovative energy storage solutions have revolutionized the way electricity is generated, transmitted, and distributed. In automation, the fusion of robotics, industrial control systems, and artificial intelligence has optimized efficiency, precision, and productivity across various industries. The integration of renewable energy sources, powered by cutting-edge developments in power electronics and smart energy management, has paved the way for cleaner and more sustainable energy landscapes. By examining historical milestones, technological innovations, and emerging trends, this article highlights the pivotal role of electrical engineering in modern society and its capacity to drive global progress. The review also discusses the challenges of modern infrastructure, the intermittency of renewable energy, and cybersecurity threats in connected systems. Finally, it outlines future directions, emphasizing the need for interdisciplinary collaboration and innovative solutions to achieve efficient, resilient, and sustainable electrical systems.